2014
DOI: 10.1007/5584_2014_34
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Tract Infections in Children in Primary Healthcare in Poland

Abstract: Respiratory tract infections are the most common diseases in children. The aim of the study was to assess their frequency and antibiotic treatment in Poland. We retrospectively analyzed 91 randomly-selected children aged 0-17 years receiving care from birth in a large primary healthcare establishment in the city of Wroclaw in Poland. Respiratory tract infections were responsible for 25-40 % of all primary healthcare visits. The median of visits due to upper respiratory tract infections was 1.8 per year in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Clinical and laboratory data of 2464 patients with a positive m-RT-PCR-ELISA result were collected additionally. To our knowledge, this is one of the largest evaluated cohorts of hospitalized children with acute respiratory tract infection [18][19][20][21][22]. The material collection was done per nasal swab or nasopharyngeal aspirate (NPA).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and laboratory data of 2464 patients with a positive m-RT-PCR-ELISA result were collected additionally. To our knowledge, this is one of the largest evaluated cohorts of hospitalized children with acute respiratory tract infection [18][19][20][21][22]. The material collection was done per nasal swab or nasopharyngeal aspirate (NPA).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial URTI requires antibiotic treatment. However, the overuse of antibiotics in children with acute upper respiratory tract infection is serious ( Cheng et al, 2019 ; Kuchar et al, 2015 ; Trinh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have suggested that both exercise (i.e., physical work) and cold (e.g., air temperature below 12 o C) may be potentially immunosuppressive, and in combination may contribute to meaningful reductions in immunity and increased risk of respiratory infection, especially for people working in some occupations (e.g., construction, fishing, food processing) [2,6,7,8,9]. In line with this, it has been shown that people working in cold environments suffer upper respiratory tract infections more frequently (URTI; including the common cold, pharyngitis, epiglottitis and laryngotracheitis) than the general population [10,11], for which respiratory tract infections are the most frequent cause of illness [12,13]. Since URTI is highly prevelant, it is important to find markers linked -directly or indirectly -to these infections with the aim of performing future interventions to reduce the prevelance and/or duration of illness.…”
Section: Introductionmentioning
confidence: 96%